Organic–inorganic hybrid salt and mixed ligand Cr(III) complexes containing the natural flavonoid chrysin: Synthesis, characterization, computational, and biological studies - Alem, Mamaru Bitew; Desalegn, Tegene; Damena, Tadewos; Bayle, Enyew Alemayehu; Koobotse, Moses O.; Ngwira, Kennedy J.; Ombito, Japheth O.; Zachariah, Matshediso; Demissie, Taye B. (Frontiers in Chemistry, 2023)
Organic–inorganic hybrid salt and mixed ligand Cr(III) complexes (Cr1 and Cr2) containing the natural flavonoid chrysin were synthesized. The metal complexes were characterized using UV-Vis, Fourier-transform infrared, MS, SEM-EDX, XRD, and molar conductance measurements. Based on experimental and DFT/TD-DFT calculations, octahedral geometries for the synthesized complexes were suggested. The powder XRD analysis confirms that the synthesized complexes were polycrystalline, with orthorhombic and monoclinic crystal systems having average crystallite sizes of 21.453 and 19.600 nm, percent crystallinities of 51% and 31.37%, and dislocation densities of 2.324 × 10−3 and 2.603 × 10−3 nm-2 for Cr1 and Cr2, respectively. The complexes were subjected to cytotoxicity, antibacterial, and antioxidant studies. The in vitro biological studies were supported with quantum chemical and molecular docking computational studies. Cr1 showed significant cytotoxicity to the MCF-7 cell line, with an IC50 value of 8.08 μM compared to 30.85 μM for Cr2 and 18.62 μM for cisplatin. Cr2 showed better antibacterial activity than Cr1. The higher EHOMO (−5.959 eV) and dipole moment (10.838 Debye) values of Cr2 obtained from the quantum chemical calculations support the observed in vitro antibacterial activities. The overall results indicated that Cr1 is a promising cytotoxic drug candidate.